Pengawasan Pendidikan dalam Perspektif Al-Qur'an dan Hadits - Noer Rohmah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2019)
In leadership, the process of supervision or ar-riqobah is a must and must be implemented. This activity is to examine and check whether the implementation of planning tasks is actually done or not. This is also to find out whether there are irregularities, misuse and shortcomings in its implementation. If there are problems, then it needs to be revised. The function of supervision or control is activities to carry out repairs rather than activities to find fault. To be able to carry out supervision properly, the planning concept must be present and clear. Without planning, it is difficult to detect irregularities and without knowledge of irregularities, the control function will be very blurred.